APLIKASI INFORMASI OBJEK WISATA DI PURWOKERTO BERBASIS MULTIMEDIA INTERAKTIF - Difla Mazidah Al 'Arifah; Adhe Nuzula Ramadlana; Denis Oktawandira; M. Aldi Yudhi Pradana; Agung Irman Syaifudin; Dasril Aldo (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
The rapid development of technology and science produces new innovations that are constantly changing for the better. One of them is in the field of information technology, especially multimedia-based technology which has an important role in the process of distributing information.Tourism is one of the leading sectors for Indonesia which plays an important role in increasing income. Indonesia as a developing country that has tourism potential, both natural, historical, cultural and religious tourism, because Indonesia has various ethnic groups, customs, and cultures so that it is quite potential to be developed properly. However, the Covid-19 pandemic which lasted from the beginning of 2019 until now has made the number of tourists in Central Java decrease. The city of Purwokerto is a city that is geographically located right under the foot of Mount Slamet which makes the city have a fairly cool and still fresh air. Purwokerto has a number of tourist attractions that offer natural beauty that makes this city even more interesting to visit. However, not a few tourists who visit the City of Purwokerto have difficulty in getting information about tourist attractions. Therefore, the "Purwokerto Object Information Application Based on Interactive Multimedia" was built to convey information to the public about tourism in Purwokerto as well as a form of promotion of tourism objects in Purwokerto. The method used in designing this interactive multimedia-based information application is themethod Waterfall. Keyword: information, multimedia, interactive, Purwokerto, tour